Milk: the new white gold? Milk production options for smallholder farmers in Southern Mali - Ridder, N. de; Sanogo, O.M.; Rufino, Mariana C.; Keulen, H. van; Giller, Kenneth E. (Elsevier, 2015)
Until the turn of the century, farmers in West Africa considered cotton to be the 'white gold' for their livelihoods. Large fluctuations in cotton prices have led farmers to innovate into other business including dairy. Yet the productivity of cows fed traditional diets is very poor, especially during the long dry season. This study combines earlier published results of farmer participatory experiments with simulation modelling to evaluate the lifetime productivity of cows under varying feeding strategies and the resulting economic performance at farm level. We compared the profitability of cotton production to the innovation of dairy. The results show that milk production of the West African Méré breed could be expanded if cows are supplemented and kept stall-fed during the dry season. This option seems to be profitable for better-off farmers, but whether dairy will replace (some of) the role of cotton as the white gold for these smallholder farmers will depend on the cross price elasticity of cotton and milk. Farmers may (partly) replace cotton production for fodder production to produce milk if the price of cotton remains poor (below US$0.35/kg) and the milk price relatively strong (higher than US$0.38/kg). Price ratios need to remain stable over several seasons given the investments required for a change in production strategy. Furthermore, farmers will only seize the opportunity to engage in dairy if marketing infrastructure and milk markets are further developed.